2010
DOI: 10.1159/000320770
|View full text |Cite
|
Sign up to set email alerts
|

Prolapse of Intussusception through the Anus as a Result of Sigmoid Colon Cancer

Abstract: Adult intussusception is rare and most often associated with cancer. We report a case of intussuscepted sigmoid colon into the rectum protruding from the anus of a 47-year-old woman. The cause of the intussusception was sigmoid colon cancer. We removed the intussuscepted part of the sigmoid colon as well as the rectum and regional lymph nodes. The patient recovered uneventfully and there has been no evidence of recurrence of the cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…The duration of symptoms is longer in enteric and benign lesions than in malignant and colonic ones [ 13 ]. In our case, intussusception of the sigmoid colon into the rectum is was secondary to a colonic lipoma, however a review of the literature demonstrated that, other lesions in the sigmoid wall are more likely to cause intussusception, such as sigmoid polyp [ 11 ], a sigmoid adenocarcinoma [ 14 , 15 ] and a sigmoid liposarcoma [ 12 ].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The duration of symptoms is longer in enteric and benign lesions than in malignant and colonic ones [ 13 ]. In our case, intussusception of the sigmoid colon into the rectum is was secondary to a colonic lipoma, however a review of the literature demonstrated that, other lesions in the sigmoid wall are more likely to cause intussusception, such as sigmoid polyp [ 11 ], a sigmoid adenocarcinoma [ 14 , 15 ] and a sigmoid liposarcoma [ 12 ].…”
Section: Discussionmentioning
confidence: 94%
“…Surgical resection is the recommended treatment when lipomas are complicated by intussusception or bowel obstruction [ 6 , 11 , 13 ]. Reduction of the intussusception is not recommended in the presence of inflammation or ischemia of the bowel wall or when a malignancy is suspected because of the high risk of perforation and dissemination of malignant cells [ 6 , 15 ]. Small intestinal lesions are mostly begnin; reduction can be attempt if there are no signs of bowel ischemia, in order to prevent the development of short bowel syndrome [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…It occurred to the patient who had fallen down on the floor in a sitting position. There was no severe abdominal pain and no history of repeated episodes of colicky pain, as usually happens in intussusception case [3].…”
Section: Case Presentationmentioning
confidence: 89%
“…Reduction can be attempted in small bowel if the segment involved is viable or malignancy is not suspected. 16…”
Section: Discussionmentioning
confidence: 99%